Literature Study: The Value Of the Character Of Love For the Motherland In Science Learning - Wazha Bickie Maundeni (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of conducting this literature study research is to discover the character of students' love for the motherland in science learning. Methodology: The method used in this research is a literature review. This study was conducted by reviewing 25 articles on the topic under study. Data analysis was carried out in this study using a synthetic matrix. The synthesis matrix is a technique for processing literature study data by interpreting it in diagrams or tables. Main Findings: The character of love for the motherland is a character that shapes students' attitudes to have a sense of nationalism, compassion, and respect for the country. Love for the homeland is perfect to be implemented in science learning, so it can make students appreciate everything done in learning and put forward common interests. A sense of love for the motherland in science learning must be instilled in children early to become human beings who can respect their nation and country. With love for the motherland, students prioritize public interests that are group in nature compared to personal interests. Novelty/Originality of this study: A literature study on love for the motherland will show the importance of the character values of love for the homeland in science learning. So the character of love for the motherland is essential for students.